Design and Development of a Semi-automated Machine in Producing Multi-Biscuit for Small Industries: Semi-Automated Multi-biscuit machine - Zulkafle, Zulhanif; Yusof, Mohd Sallehuddin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This project was carried out to develop a prototype semi-automated multi-biscuit machine kuih semperit and biscuit badam, bangkit and mama carey maker using roller stamp mechanism for small and medium entrepreneurs (SMEs). The main function of this machine is to produce a high rate of production of kuih semperit and biscuit badam, bangkit and mama carey. This machine consists of several key components which are motor, conveyors, two different types of rollers, and cutter. The roller and the conveyor are driven by two different motors [1]. This integrates the previous machine to increase production rate, reduce the processing time and save human power usage. Descriptions are shown in this report. In this project, a series of analyses are carried out, the analysis was production cost analysis, production rate analysis, and breakeven analysis. Based on production rate analysis, the product can be increased to 45 000 to 46 000 pieces per month and net profit was RM4 900 to RM5 400 per month.